2007
DOI: 10.2741/2430
|View full text |Cite
|
Sign up to set email alerts
|

Towards a quantitative perception of human-microbial co-evolution

Abstract: The influence of changes in population structures of modern humans and human pathogens is likely reciprocal. In my opinion, a quantitative approach to study this co-influence in a historical perspective requires, in particular, adequate estimators of genetic distances that are well developed for human but not yet for microbial populations. Here, I propose a simple measure of genetic distance between geographic populations within a microbial species based on the observed difference in the frequencies of its gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Comparison with global M. tuberculosis database SITVIT2 (Institut Pasteur de Guadeloupe) and MIRU database of the Beijing genotype (Mokrousov, 2007, 2008) revealed that the 12‐MIRU profile 223325173533 [type MIT17 (SITVIT2) or M11 (Mokrousov, 2008)] was found in 27/41 Beijing strains, and profile 223325153533 [type MIT16 (SITVIT2) or M2 (Mokrousov, 2008)] in 7/41 Beijing strains in our study. Both types are predominant in different Russian settings although at different ratios.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Comparison with global M. tuberculosis database SITVIT2 (Institut Pasteur de Guadeloupe) and MIRU database of the Beijing genotype (Mokrousov, 2007, 2008) revealed that the 12‐MIRU profile 223325173533 [type MIT17 (SITVIT2) or M11 (Mokrousov, 2008)] was found in 27/41 Beijing strains, and profile 223325153533 [type MIT16 (SITVIT2) or M2 (Mokrousov, 2008)] in 7/41 Beijing strains in our study. Both types are predominant in different Russian settings although at different ratios.…”
Section: Discussionsupporting
confidence: 54%
“…2). Finally, ST42 is found virtually in all areas compared here, both former Soviet Union and northern Europe (with the exception of Germany 4 (2) 1-4 (2-3) 0.548 (0.048) MIRU20 2 (1) 1-2 (2) 0.022 (0) MIRU23 5 (1) 1-6 (5) 0.224 (0) MIRU24 1 (1) 1 (1) 0 (0) MIRU26 6 (2) 1-7 (5-7) 0.714 (0.621) MIRU27 1 (1) 3 (3) 0 (0) MIRU31 4 (1) 2-5 (5) 0.656 (0) Comparison with global M. tuberculosis database SIT-VIT2 (Institut Pasteur de Guadeloupe) and MIRU database of the Beijing genotype (Mokrousov, 2007(Mokrousov, , 2008 revealed that the 12-MIRU profile 223325173533 [type MIT17 (SIT-VIT2) or M11 (Mokrousov, 2008)] was found in 27/41 Beijing strains, and profile 223325153533 [type MIT16 (SITVIT2) or M2 (Mokrousov, 2008)] in 7/41 Beijing strains in our study. Both types are predominant in different Russian settings although at different ratios.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, repetitive and insertion sequences have proven useful for studying both the epidemiology and the phylogeography of M. tuberculosis (1,2,4,(11)(12)(13)(14)(15)(16)(17)(18)(19)24), and regularly updated genetic diversity databases are available for this pathogen (3,4,7,(11)(12)(13)23).…”
mentioning
confidence: 99%